Hyers-Ulam Stability of Functional Equation Deriving from Quadratic Mapping in Non-Archimedean n,β-Normed Spaces - Nazek Alessa; K. Tamilvanan; K. Loganathan; K. Kalai Selvi (Journal of Function Spaces)
In this work, we have to introduce a generalized quadratic functional equation and derive its solution. The main objective of this work is to investigate the Hyers-Ulam stability of quadratic functional equation in non-Archimedean n,β-normed spaces.